EASI: Volume 4, Issue 1. - Samaniego Riera, Franklin (EASI: Engineering and Applied Sciences in Industry, 2025)
In a constantly evolving world, digital tools are transforming the way we teach, learn and think. In these pages, readers can explore innovations, trends and reflections on the future in the digital era.Discover inspiring articles, insightful analysis, and practical experiences for educators, students, and technology enthusiasts. Immerse yourself in the fascinating dialogue presented by EASI.